Alternatif Kebijakan Penyaluran Subsidi Pupuk Bagi Petani Pangan - Suryana, Achmad; Agustian, Adang; Yofa, Rangga Ditya (Analisis Kebijakan Pertanian, 2023)
Fertilizer is one of important production factors in food farming to gain high productivity. Efforts to manage procurement, distribution, and proper fertilizer application have been regulated, implemented, and controlled by the government. However, complaints related to fertilizer distribution problems still exist. This study aims to analyze national fertilizer performance, especially fertilizer policy for food sector, fertilizer industry, and farmer dynamics in formulating fertilizer needs and its application; and to formulate fertilizer policy alternatives that can increase fertilizer distribution efficiency and use of budget subsidy. Coverage and data of this study were at national level. Analytical methods of this study were both quantitative and qualitative descriptive approaches. The main finding of this study was a formulation of four policy alternatives pertaining distribution mean of direct fertilizer subsidy delivered to farmers. Implementation of these policy alternatives requires availability of accurate data on rice farmers, agricultural land ownership and use, and food farming system profile nationwide. In the short run, in order to increase distribution efficiency of subsidized fertilizer to farmers, it is recommended that some adjustments to the current fertilizer policy must be done on price of natural gas as raw material for Urea, level of subsidized price of fertilizers paid by farmers, document of definitive plan of fertilizer needs of farmer groups (RDKK), and function of fertilizer supervision commission at regional levels. AbstrakPupuk merupakan salah satu faktor produksi penting dalam usaha tani pangan untuk memperoleh produktivitas tinggi. Upaya mengelola pengadaan, penyaluran, dan penggunaan pupuk telah diatur, dilaksanakan, dan diawasi pemerintah, namun keluhan terkait dengan permasalahan penyaluran pupuk bersubsidi masih saja terjadi. Pengkajian ini bertujuan untuk menganalis keragaan perpupukan nasional, terutama kebijakan penyaluran pupuk bersubsidi untuk subsektor pangan, industri pupuk nasional, dan dinamika petani dalam penyusunan kebutuhan serta pemanfaatan pupuk; dan merumuskan alternatif kebijakan perpupukan yang dapat meningkatkan efisiensi dalam penyaluran dan anggaran subsidi pupuk. Cakupan kajian dan data yang digunakan adalah pada tingkat nasional. Metode kajian menggunakan analisis kuantitatif dan deskriptif kualitatif. Hasil utama kajian ini berupa formulasi empat alternatif kebijakan cara penyaluran anggaran subsidi pupuk langsung diberikan kepada petani. Implementasi alernatif kebijakan tersebut mempersyaratkan tersedianya data yang akurat tentang petani padi, penguasaan dan pengusahaan lahan pertanian, dan profil usaha tani pangan secara nasional. Dalam jangka pendek, untuk meningkatkan efisiensi penyaluran pupuk bersubsidi ke petani disarankan dilakukan beberapa penyesuaian atas kebijakan perpupukan saat ini, yaitu harga gas bumi sebagai bahan baku Urea, harga eceran tertinggi pupuk bersubsidi, dokumen rencana definitif kebutuhan kelompok (RDKK), dan fungsi komisi pengawasan pupuk di daerah.
Keywords: subsidized fertilizer; direct subsidy; distribution efficiency; food farmer; pupuk bersubsidi; subsidi langsung; efisiensi distribusi; petani pangan